Religiously Grounded Character and Its Association with Subjective Well-Being in Emerging Adults: A Latent Profile Analysis - Daniela Villani; Sara Eissa; Michela Zambelli; Anna Flavia Di Natale (Religions, 2025)
Subjective Well-Being (SWB) is a central indicator of mental health and overall quality of life in emerging adulthood; religiosity can contribute to this outcome. Emerging research suggests that religious identity and virtues not only can contribute independently to SWB but may work together in shaping it. Given this interplay, the present study adopts a person-centered approach, using Latent Profile Analysis (LPA), to investigate profiles of emerging adults showing a similar configuration of religious identity and virtues and to examine their contribution to SWB. Two-hundred and ninety-one emerging adults living in Italy aged 18 to 30 completed an online survey asking for various demographic variables, religious status, religious affiliation, religious practices, religious identity (U-MICS Religious domain), character strengths and virtues (VIA- IS), and subjective well-being (SWLS and SPANE). A best-fitting model consisting of three distinct, non-overlapping profiles, each demonstrating a unique configuration of religious identity dimensions (commitment, in-depth exploration, reconsideration) and virtues (Transcendence, Humanity, Temperance), emerged. These profiles were differently associated with SWB. Specifically, individuals in the Engaged with High Religious Virtues profile displayed high levels of religious commitment and exploration, paired with high levels of religious virtues, particularly Transcendence, and exhibited the highest levels of SWB. These findings suggest that religious identity and virtues are strictly intertwined and that higher levels of this conjoint integration correspond to greater SWB. Future interventions aimed at fostering religious self-exploration and cultivating religiously grounded virtues can be particularly effective at this stage of the life cycle.